Two Alternatively Spliced Transcripts from the Drosophila period Gene Rescue Rhythms Having Different Molecular and Behavioral Characteristics - Cheng, Yuzhong (American Society for Microbiology, 1998)
The period (per) and timeless (tim) genes encode key components of the circadian oscillator in Drosophila melanogaster. The per gene is thought to encode three transcripts via differential splicing (types A, B, and C) that give rise to three proteins. Since the three per mRNA types were based on the analysis of cDNA clones, we tested whether these mRNA types were present in vivo by RNase protection assays and reverse transcriptase-mediated PCR. The results show that per generates two transcript types that differ only by the presence (type A) or absence (type B′) of an alternative intron in the 3′ untranslated region. Transgenic flies containing transgenes that produce only type B′ transcripts (per(B′)), type A transcripts (per(A)), or both transcripts (per(G)) rescue locomotor activity rhythms with average periods of 24.7, 25.4, and 24.4 h, respectively. Although no appreciable differences in type A and type B′ mRNA cycling were observed, a slower accumulation of PER in flies making only type A transcripts suggests that the intron affects the translation of per mRNA.